Transforming Student Evaluation Policy through the Student Satisfaction Index on Lecturer Performance: Strengthening Learning Governance - Mujazi; Muhammad Soleh Hapudin; Ainur Rosyid (International Journal of Education and Teaching Zone, 2026)
Student evaluation data are often underutilized in higher education despite their potential to support evidence-based academic decision-making. The Student Satisfaction Index on Lecturer Performance (IKMKD), which measures teaching quality from students’ perspectives, has received insufficient attention as a tool for study program governance and quality improvement. This study looks at how the IKMKD can be used not only as a tool for evaluation but also as a basis for policies to improve academic management in the Elementary School Teacher Education program at Universitas Esa Unggul, Indonesia. The study employed a convergent parallel mixed-methods design involving 399 students across five academic semesters. Data were collected through IKMKD questionnaires and semi-structured interviews using purposive sampling. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using thematic analysis to explore students' evaluation experiences and perceptions of teaching practices. The findings indicate that the average IKMKD score reached 3.51, which falls within the good category, indicating that students generally perceived lecturers’ teaching performance positively across key aspects of the learning process. Nevertheless, several recurring issues were identified, including unclear assignment instructions, limited transparency in grading criteria, delayed feedback, and inconsistent lecture schedules. The value of IKMKD as a data-informed feedback mechanism that can support pedagogical improvement, lecturer development, and continuous quality enhancement at the study program level.